BASIC PRINCIPLES OF RASASHASTRA – THE INDIAN PHARMACEUTICS OF HERBO-MINERAL PREPARATIONS - Rajput Dhirajsingh; Suryavanshi Pradeep; Suryavanshi Sandip; Suryavanshi Shweta (International Journal of Applied Ayurved Research, 2016)
Basic principles are the fundamental concepts which have been repeatedly tested in various ways and are essential to understand related science. Every science has its own fundamental principles. Rasashastra, a branch of Ayurveda is considered as Indian pharmaceutics of herbo-mineral preparations. The principles associated with foundation and developments of Rasashastra are not clearly indicated and are scattered in various ancient classical texts. Therefore an attempt has been made to review of these fundamental principles in systemic and explanatory way. Therefore in present work an attempt has been made to make a comprehensive review of basic principles of Rasashastra and to elucidate their distinguishing features. Lohavada and Dehavada; eighteen processing methods of mercury, terminology in Rasashastra, instruments, crucibles, blowers and pit for incineration of metals/minerals, purification, incineration, Amritikarana, test for incinerated materials and levigation are the eight basic principles of Rasashastra. Complete understanding of these concepts with view of both Ayurvedic and contemporary science is the key for research and development in Rasashastra.